Performance of a Rotational Sensor to Decipher Volcano Seismic Signals on Etna, Italy. Issue 6 (9th June 2022) - Eibl, Eva P. S.; Rosskopf, Martina; Sciotto, Mariangela; Currenti, Gilda; Di Grazia, Giuseppe; Jousset, Philippe; Krüger, Frank; Weber, Michael
Abstract: Volcano‐seismic signals such as long‐period events and tremor are important indicators for volcanic activity and unrest. However, their wavefield is complex and characterization and location using traditional seismological instrumentation is often difficult. In 2019 we recorded the full seismic wavefield using a newly developed 3C rotational sensor co‐located with a 3C traditional seismometer on Etna, Italy. We compare the performance of the rotational sensor, the seismometer and the Istituto Nazionale di Geofisica e Vulcanologia‐Osservatorio Etneo (INGV‐OE) seismic network with respect to the analysis of complex volcano‐seismic signals. We create event catalogs for volcano‐tectonic (VT) and long‐period (LP) events combining a STA/LTA algorithm and cross‐correlations. The event detection based on the rotational sensor is as reliable as the seismometer‐based detection. The LP events are dominated by SH‐type waves. Derived SH phase velocities range from 500 to 1, 000 m/s for LP events and 300–400 m/s for volcanic tremor. SH‐waves compose the tremor during weak volcanic activity and SH‐ and SV‐waves during sustained strombolian activity. We derive back azimuths using (a) horizontal rotational components and (b) vertical rotation rate and transverse acceleration. The estimated back azimuths are consistent with the INGV‐OE event location for (a) VT events with an epicentral distance larger than 3 km and some closer events, (b) LP events and tremor in the main crater area. Measuring the full wavefield we can reliably analyze the back azimuths, phase velocities and wavefield composition for VT, LP events and tremor in regions that are difficult to access such as volcanoes. Plain Language Summary: Traditional seismographs usually include mass and spring systems which measure vibrations constrained to up‐down, north‐south and east‐west directions. We compare the traditional seismometer to a rotational sensor which measures ground rotation around the same three directions. We installed a rotational sensor on Etna volcano in 2019 to test these new sensors in a volcanic environment. We compare the performance of the rotational sensor, a traditional seismometer and the Istituto Nazionale di Geofisica e Vulcanologia‐Osservatorio Etneo (INGV‐OE) seismometer network. We detect two types of a few second long earthquakes and find that the rotational sensor performs as good as the seismometer. We use the rotational sensor to calculate directions of the earthquake locations and find that most directions agree with the INGV‐OE network location and the area of the active craters. We find that for some earthquakes the ground only moved horizontally while for others it also moved up and down. Using a rotational sensor on a volcano we can easily and reliably estimate the ground motion, the speed of the earthquake waves in the ground and understand better how these earthquakes are generated. Key Points: We tested the performance of a rotational sensor compared to a seismometer and a seismic network using long‐period (LP), volcano‐tectonic (VT) events and tremor on Etna LP and VT events are dominated by SH‐ and SV‐waves, respectively. Tremor changed from SH‐ to a mixed wavefield during strombolian eruptions LP event and tremor back azimuths point to the main craters consistent with the Istituto Nazionale di Geofisica e Vulcanologia location; VT event back azimuths are at times consistent